Um estudo sobre a aprendizagem dos números racionais à luz da Teoria dos Registros de representação semiótica - Padilla, Alexandre (2019)
This research addresses the teaching-learning process of rational numbers in its different representations from work activities in the classroom. The theoretical contribution is supported in theory of Semiotic Representation records for Raymond Duval (2009). It is used to analyze a task sequence drawn from official documents and textbooks. The goal of this investigation is to check how the mobilization of different representations of the same object, can contribute to the acquisition of concepts related to rational numbers with greater articulation between the fractional representation and the decimal representation. Our own research practice was done based on a qualitative research. It was observed the development of students in the seventh grade of primary education in a school in the city of São Paulo, considering the difficulties presented by them in relation to the rational numbers. These challenges sometimes stretch for all education and can lead to a Constitution of mechanized concepts and without meaning. With the analysis of the initial protocols, the difficulties presented by the students in the different representations of the same object, difficulties related to the apprenticeship of the rational numbers. It is concluded that the theory of Duval (2009) can contribute to the teaching-learning process of this theme.